Learning Agility of Human Resources at State-owned Banks in the City of Makassar - Megawaty; Vira Fenita Mahmuddin; Hendriadi (IECON: International Economics and Business Conference, 2023)
Companies are trying to prepare their organizations to face the challenges in the VUCA era. The influence of VUCA also influences the field of human resources. Talented employees become superior and change changers. To deal with situations full of uncertainty requires learning agility, namely individuals who can survive, where they can adapt and are able to learn quickly from existing experiences and opportunities and are able to apply what they have learned to gain success in new situations. This study aims to analyse the level of learning agility of human resources at state-owned banks in the city of Makassar. The analytical method used in this study is a quantitative descriptive analysis method using the three box method analysis tool. Questionnaires were distributed to 100 respondents who are employees of state-owned banks in the city of Makassar. The results of this study indicate that the learning agility level of human resources at State-owned banks in Makassar city is in the medium learning agility level category.